An abundant porous biochar material derived from wakame (Undaria pinnatifida) with high adsorption performance for three organic dyes - Yao, Xinxin; Ji, Lili; Guo, Jian; Ge, Shaoliang; Lu, Wencheng; Chen, Yingna; Cai, Lu; Wang, Yaning; Song, Wendong (Bioresource technology, 2020)
[Display omitted] •A one-step pyrolysis/activation method was used to prepare wakame biochar (AWBM).•AWBM has abundant mesopores with a high specific surface area (1156.25 m2/g).•At 293 K, the adsorption of MG using AWBM can reach 4066.96 mg/g.•The adsorption of dyes using AWBM contain physical and chemical adsorption. In this study, an activated wakame biochar material (AWBM) was prepared by a one-step calcination and activation method, whose adsorption performances for methylene blue (MB), Rhodamine B (RB) and malachite green (MG) were also analyzed. The results showed AWBM was a mesoporous fluffy structure material with a higher specific surface (1156.25 m2/g), exhibiting superior adsorption capacities for MB (841.64 mg/g), RB (533.77 mg/g) and MG (4066.96 mg/g), respectively. In addition, FT-IR analysis showed that AWBM possessed abundant active groups (such as –OH, –CO and –CH), further enhancing the adsorption efficiencies. The Langmuir model could better fit the three dyes adsorption isotherms process using AWBM, and the Pseudo-second-order model could better describe the adsorption kinetic experimental data. The thermodynamic analysis showed that the three dyes adsorption using AWBM was spontaneous endothermic reaction. This study suggests AWBM has enormous potential in the application of removing organic dyes from wastewater.